Enforcement Issues in the Governance of Ships’ Carbon Emissions - Michael Bloor; Susan Baker; Helen Sampson; Katrin Dahlgren (Laws, 2015)
The shipping industry, although relatively carbon-efficient, is projected to produce rising carbon emissions in the future as a consequence of increasing world trade. A number of candidate regulations designed to mitigate these emissions have been canvassed by the UN’s International Maritime Organisation and by the European Commission. Many of these schemes are focussed on the use of market measures—emission trading schemes or fuel levies. This paper draws on observational and interview data gathered to examine enforcement issues associated with the control of ships’ sulphur emissions in order to consider the possible enforcement problems that might be associated with projected market measures to control ships’ carbon emissions. Enforcement problems are shown to be associated with the globalised character of the industry and its polycentric governance structure.